Legal Analysis of The Criminal Act of Domestic Violence according to Law No. 23 of 2004 (Case Study of Decision Number 314/PID.SUS/2023/PN.SKT) - Rossi Fitrianingrum; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
Domestic Violence (KDRT) is a problem that impacts the physical and mental health of the victim. UU no. 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) as a legal instrument to protect victims and take action against perpetrators. This research analysis decision number 314/Pid.sus/2023/PN.Skt to evaluate the effectiveness of the implementation of the PKDRT Law. This research aims to analyze the form and application of law regarding domestic violence in accordance with the PKDRT Law in the case of Decision number: 314/Pid.Sus/2023/PN.Skt. In this way, this research can provide a deeper understanding of the causes and efforts to prevent domestic violence in accordance with applicable laws in Indonesia. This research uses normative juridical methods with a descriptive analysis approach to examine the implementation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Data was collected through literature study which includes primary, secondary and tertiary legal materials. In Decision Number 314/Pid.Sus/2023/PN.Skt it is in accordance with legal provisions, but the sentence imposed is relatively light and does not provide a maximum deterrent effect. Apart from that, protection for victims after the incident still needs to be improved, especially in psychological aspects and ensuring safety. Therefore, synergy is needed between law enforcement and social protection mechanisms so that the objectives of the PKDRT Law in preventing and overcoming domestic violence can be realized. To prevent domestic violence, joint efforts from various parties are needed through education, public awareness, support for victims, intervention against perpetrators, and strict law enforcement. Prevention can also be done by strengthening moral values, religion and mutual respect in the family.